Emerald Ash Borer: A Potential Future Threat to Ash Trees in Florida - Don Spence; Jason Smith (EDIS)
Do not move firewood into or around the state! This invasive exotic beetle kills ash trees and is likely to reach Florida in the years to come — or faster if it gets transported by humans. Learn more in this 5-page fact sheet was written by Don Spence and Jason Smith and published by the UF Department of School of Forest Resources and Conservation, August 2011. Reviewed August 2014.